PENGARUH KOPERASI DAN USAHA MIKRO KECIL MENENGAH TERHADAP KESEJAHTERAAN MASYARAKAT DI KABUPATEN BERAU - Jaya Krisma (ECO-BUILD, 2026)
The purpose of this research is to determine the effect of cooperatives and micro, small, and medium enterprises (MSMEs) on community welfare in Berau Regency. This study applies a quantitative method using secondary time series data from 2015 to 2024. The analytical model used is multiple linear regression. The results show that the hypotheses are rejected. Partially, the number of cooperatives does not have a significant effect on community welfare, as indicated by the t-test significance value of 0.951 > 0.05. Likewise, the number of MSMEs also does not have a significant partial effect on community welfare, with a t-test significance value of 0.051 > 0.05. Simultaneously, both the number of cooperatives and MSMEs do not have a significant effect on community welfare, as shown by the F-test significance value of 0.56 > 0.05. This indicates that the quantity of business units alone is not sufficient to improve welfare without improvements in quality, productivity, and effectiveness of economic activities.